Sustainability with Changing Climate and Extremes - Yan, Xiaodong; Yang, Jia; Jin, Shaofei (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on the up-to-date studies on the sustainability with changing climate and extremes. The main contributors discussed the changing climate and extreme events, as well as their impacts on natural and human dimension sustainability, including the incorporated social-ecologic and socioeconomic processes. Special attention is given to four main sections: natural disasters in agriculture; urban/rural ecosystem, tourism, and ecosystem service; extreme climate indices, and newly created dataset for climate change.